Effectiveness of Intradialytic Resistance Training on Muscle Mass and Strength in Patients on Hemodialysis - Sandra Vasquien; I Ketut Swarjana; A.A.A. Yuliati Darmini; I Nyoman Arya Maha Putra (Fakultas Ilmu Keperawatan Universitas Indonesia, 2025)
Hemodialysis (HD) patients with chronic kidney disease (CKD) lose muscle mass and strength due to protein energy wasting (PEW). The purpose of this study was to test the effectiveness of intradialytic resistance training (IRT) in increasing muscle mass and strength. It used a pre-experimental, one-group pretest-posttest design. Based on a sample size estimate using G*power software, 33 CKD patients undergoing HD at a private hospital in Bali were included. The patients were selected using purposive sampling. Muscle mass was measured using Bioelectrical Impedance Analysis (BIA), while muscle strength was measured using the Medical Research Council Muscle Scale. The Wilcoxon test evaluated IRT's efficacy on muscle strength, while the dependent samples t-test evaluated its impact on muscle mass. The results of this study found that IRT had no effect on muscle mass, with a mean difference of -0.330 (p = 0.274). On the contrary, IRT significantly improved muscle strength (p = 0.018). In conclusion, IRT proved beneficial for strengthening muscle but not for gaining muscle mass. Therefore, to improve muscle strength, patients with CKD undergoing HD are advised to actively perform IRT under supervision for a minimum of 30 minutes per day. Keywords: intradialytic resistance training, muscle mass, muscle strength, protein energy wasting Abstrak Efektifitas Intradialytic Resistance Training Terhadap Massa dan Kekuatan Otot Pasien dengan Hemodialisis. Pasien hemodialisis (HD) dengan Penyakit Ginjal Kronis (PGK) kehilangan massa dan kekuatan otot yang disebabkan oleh Protein Energy Wasting (PEW). Tujuan penelitian ini adalah untuk menguji efektifitas Intradialytic Resistance Training (IRT) terhadap peningkatan massa dan kekuatan otot. Penelitian ini menggunakan pre-experimental one-group pretest, post-test design. Berdasarkan perhitungan besar sampel menggunakan G*Power Software, 33 pasien PGK yang menjalani HD di sebuah rumah sakit swasta di Bali terlibat dalam penelitian ini. Pasien dipilih menggunakan teknik purposive sampling. Massa otot diukur menggunakan Bioelectrical Impedance Analysis (BIA), sedangkan kekuatan otot menggunakan Medical Research Council Muscle Scale. Uji efektifitas kekuatan otot menggunakan Wilcoxon test, sedangkan t-test digunakan untuk menguji efektifitas massa otot. Hasil penelitian menunjukan IRT tidak efektif dalam meningkatkan massa otot, dengan mean -0,330 (p = 0,274). Namun, IRT terbukti efektif dalam mening-katkan kekuatan otot, (p = 0,018). Kesimpulannya, IRT bermanfaat untuk meningkatkan kekuatan otot, tetapi tidak untuk meningkatkan massa otot. Oleh karena itu, untuk meningkatkan kekuatan otot, pasien PGK yang menjalani HD disarankan aktif melakukan IRT dengan pengawasan minimal 30 menit dalam sehari. Kata Kunci: intradialytic resistance training, kekuatan otot, massa otot, protein energy wasting